Produksi Ion Nitrogen dalam Reaktor Plasma Lucutan Pijar Korona Konfigurasi Multi Titik Bidang dan Pemanfaatan untuk Pengayaan Nitrogen pada Pupuk Kompos - Nur, Muhammad; Nugroho, Irfan Wahyu; Muchlisin, Zaenul; LatifNitrogen ions have been generated in the air by corona glow discharge plasma. The, Sjafrul (JURNAL SAINS DAN MATEMATIKA, 2011)
Nitrogen ions have been generated in the air by corona glow discharge plasma. The unipolar current sturation of Sigmond has been observed and nitrogen ions were used for enrichment of nitrogen in compost of palm oil empty fruit bunches. Generator of ions was a positive corona discharge plasma with multi point to plane electrodes configurations and by using a DC voltage source of 6.8 kV and 8 mA. In the glow discharge plasma condition, the nitrogen ions were produced in air. Implantation of nitrogen ions can increase the levels of nitrogen in the compost. The highest percentage of nitrogen is obtained in the series of experiment for time of radiation was 100 minutes. The amount of mass percentage of nitrogen in the enrichment compost was (3.4 ± 0.3) % and we compare with compost control without ions radiation was 1.1 % (mass percentage). It can be concluded that the increasing of nitrogen content in the compost can be done by almost 300 % . Key words : corona glow discharge plasma, compost, nitrogen ionic